The information content of the Fourier coefficients in the authentication by the iris of the eye - Швец, Валериян Анатольевич; Фесенко, Андрей Алексеевич; Фесенко, Владислав Алексеевич; Швец, Александр Валериянович; Швец, Валериан Валериянович (Ukrainian Information Security Research Journal, 2017)
Authentication of a person without a doubt is an actual problem, a practical solution which employs thousands and millions of people worldwide. Automation of this process is an important component of the development of modern society. The tasks of authentication and identification of the person now being done with automatic biometric systems, constituting one of the new areas of applied mathematics, biometrics identification. In the biometric authentication detection iris today recognized as the leader in accuracy and reliability among biometric characteristics. Analyzing the disadvantages of processing the iris of the eye the mathematics of Gabor. This paper proposes a new selection method of informative features from the image of the iris the Fourier transform. Distinguishing feature of different irises are encouraged to use the envelope of the Fourier coefficients. The results showed that the envelope of the Fourier coefficients quite informative and has pronounced maxima, the large variation in amplitude and has a clear distinction for images of iris of different people. The advantage of the envelope of the Fourier coefficients is that for its calculation uses only the space of Cartesian coordinates, which is natural for image processing. The envelope of the Fourier coefficients can be recommended for use in authentication by the iris of the eye.